1993
DOI: 10.3354/dao016047
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial disease of cultured giant darn Tridacna gigas larvae

Abstract: The role of bacteria in mortality of the planktonic larval stage of cultured giant clams Tridacna gigas was examined. Addltion of the antibiotic chlorarnphenicol at 5 ppm reduced larval mortality and confirmed the involvement of bacteria in disease prior to settlement. Syn~ptoms of bacterial disease were usually rapid and profuse bacterial growth on and in larval clams and disintegration of most tissues withln 48 h. Results of tests in which larvae were exposed to 10' bacteria ml-' suggested that bacteria belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…During settlement and metamorphosis, the most critical stages in larval development, larvae begin a life associated with substrate in high densities and come into contact with the resident microbiota and, hence, with putative pathogens (Sutton & Garrick 1993). All these factors can facilitate the transmission or appearance of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…During settlement and metamorphosis, the most critical stages in larval development, larvae begin a life associated with substrate in high densities and come into contact with the resident microbiota and, hence, with putative pathogens (Sutton & Garrick 1993). All these factors can facilitate the transmission or appearance of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…V. furnissii is a Gram-negative bacterium which has been associated with acute diarrhoeal illness after consumption of contaminated seafood (Brenner et al, 1983), and it has been reported to be associated with the disease of clam (Wang et al, 1992). V. fluvialis, V. cincinnatiensis, V. mimicus, and V. metschnikovii have also been associated with bivalves (Montilla et al, 1994;Maugeri et al, 2000;Cavallo and Stabili, 2002;Sutton and Garrick, 1993). Although most of the species within the Cholerae clade can cause diarrhea (Sawabe et al, 2007), there are limited reports on the pathogenicity of this clade to bivalve-related species.…”
Section: Introductionmentioning
confidence: 95%
“…Tridacna gigas with infection leading to general disintegration of the tissues and 437 total mortality after exposure to 10 7 bacteria ml -1 (Sutton and Garrick, 1993). The 438 organism has been recovered from raw fish and shellfish in markets and shops, 439…”
Section: Metschnikovii Is Regarded As Potentially Pathogenic To Lamentioning
confidence: 99%